Self-Rated Depression Severity Relative to Clinician-Rated Depression Severity: Trait Stability and Potential Role in Familial Transmission of Suicidal Behavior. Issue 3 (2nd July 2016) - John Mann, J.; Ellis, Steven P.; Currier, Dianne; Zelazny, Jamie; Birmaher, Boris; Oquendo, Maria A.; Kolko, David J.; Stanley, Barbara; Melhem, Nadine; Burke, Ainsley K.; Brent, David A.
Abstract : Self-rated depression and hopelessness severity are predictors of suicide attempt in major depression. This study evaluated whether: (1) greater self-rated distress relative to severity of clinician-rated depression is a trait; (2) that trait is familial; and (3) that trait is linked to familial transmission of suicidal behavior. A total of 285 mood disorder probands and 457 offspring were assessed twice, at least 1 year apart. Family and subject intra-class correlations for self-report depression and hopelessness, controlling for clinician-rated depression severity, were computed. Mixed general linear models determined offspring-proband correlations. Within-individual intra-class correlation (ICC) for depression-hopelessness was 37.8% (bootstrap 95% CI: 31.0–46.3%). Parent-offspring ICC was 10.7% (bootstrap 95% CI: 3.5–17.8%). Suicide attempt concordant parent-offspring correlation for subjective depression was positive, but negative for attempter parent and nonattempter offspring (p = .0213 for slope interaction). Pessimism was greater in proband or offspring attempters than proband or offspring nonattempters (p < .05). Self-reported hopelessness is partly trait-dependent, and there is modest familial transmission of self-reported depression linked to suicidal behavior that may partly explain familial transmission of suicidal behavior.